Anemoside B4 targets RAGE to attenuate ferroptosis in sepsis-induced acute lung injury - Bu, Yue; Li, Zhixi; Wang, Cheng; Yu, Yongjing; Liu, Chang; Sun, Yue; Sun, Zhenyu; Gong, Weidong; Luo, Juan; Yue, Ziyong (Frontiers in Pharmacology, 2025)
IntroductionAnemoside B4 (AB4), a major bioactive saponin isolated from the roots of Pulsatilla chinensis, exhibits anti-inflammatory and antioxidant properties. While recent study has demonstrated its ability to inhibit ferroptosis in arthritis, its role in sepsis-induced acute lung injury (SALI) remains undefined. This study aims to clarify the mechanism underlying AB4’s action in SALI.MethodsTo explore the therapeutic mechanism of AB4 in SALI, an integrated approach was employed, combining network pharmacology, molecular dynamics simulation, surface plasmon resonance (SPR) assays, in vivo experiments using cecal ligation and puncture (CLP)-induced mouse models, and in vitro studies with lipopolysaccharide (LPS)-stimulated RAW264.7 cells. The therapeutic effects of AB4 on SALI were evaluated through histopathological examination, biochemical analysis, immunofluorescence staining, and Western blotting, which collectively elucidated its in vivo and in vitro mechanisms of action.ResultsAB4 ameliorated CLP-induced lung injury in mice, as evidenced by reduced pathological damage, lower injury scores, and a decreased lung wet-to-dry weight ratio. In vivo, AB4 significantly reduced levels of pro-inflammatory cytokines (IL-1β, TNF-α, and IL-6), decreased oxidative stress markers MDA and DHE, and increased GSH levels. In vitro, AB4 inhibited ferroptosis in macrophages, with a pharmacological effect comparable to the known ferroptosis inhibitor Ferrostatin-1 (Fer-1). Network pharmacology analysis identified the AGE/RAGE signaling pathway as a primary target of AB4. AB4 dose-dependently downregulated RAGE expression and restored levels of GPX4 and SLC7A11. SPR and molecular docking experiments confirmed a high affinity between AB4 and RAGE, with a dissociation constant (KD) of 3.86 μM. Consistently, co-administration of the RAGE inhibitor FPS-ZM1 effectively suppressed ferroptosis and enhanced Nrf2 activity in CLP-induced mice.ConclusionAB4 directly targets RAGE to inhibit the AGE/RAGE-Nrf2 axis, thereby suppressing both ferroptosis and inflammation in SALI. This previously unreported mechanism establishes AB4 as a novel multifaceted therapeutic candidate for SALI.